Peculiarities in the Development of Investment Processes in the Russian Arctic - Natalia A. SEROVA (Communications of International Proceedings, 2020)
The research is aimed at defining possibilities of increasing the investment activity in the Russian Arctic. It involves an economic and statistical analysis of the investment process development in the Russian Arctic for 2000-2018, including the investment structural analysis in terms of financing sources, forms of incorporation and investment media. Main trends observed in the field of investments in the studied regions and Russian Arctic in general are revealed during the research. These include a 15,3 times increase in the inflow of investments over the study period, a growing share of own funds in the cumulative investments indicative of the improvement of financial stability in the majority of arctic regions and a rising portion of investments to the core capital of joint ventures with Russian and foreign ownership that suggests an efficient development of the public and private partnership. It is concluded that the Russian Arctic has a substantial potential for the activation of investment activities.
Keywords: Arctic Zone of The Russian Federation; Regions; Investments.